The Transition of Financial Service Organisations towards Co-Creation within a Developing Country Context - QUINTERO RUBIO, PAULA VANESA (2017)
The purpose of this research is to explore the challenges of developing and implementing a co-creation process in a developing country context. Specifically, it will examine the facilitators, and constraints of this within financial service organisations operating in the context of an emerging economy. It was achieved through a single case study research design, it included semi-structured interviews for the collection of primary data and the analysis of documentation as secondary data as qualitative methods for the data collection. Concerning the data analysis, the Gioia methodology was used to build the data structure. Six 2nd-order themes were identified, and classified into three different aggregate dimensions: restructuration of processes, and areas; organisational culture’ changes; and national context. The 2nd-order themes were also analysed, and catalogued depending on whether they were facilitators or constraints to the organisation during its transition towards co-creation: restructuration of internal areas, processes simplification, better and deeper customer knowledge, and the change of the strategic model, were identifying as the facilitators, whereas the change of the commercial strategy, change of the cultural model, political/economic context, and competitors/substitutes threats, were classified as the constraints.